2017
DOI: 10.1111/fog.12230
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential habitat distribution of the neon flying squid (Ommastrephes bartramii) off the eastern coast of Japan in winter

Abstract: Habitat suitability index (HSI) models were applied to identify the potential habitat distribution of the neon flying squid (Ommastrephes bartramii) off the eastern coast of Japan during winter. We used an ocean reanalysis product, a satellite-derived dataset,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The HSI model has been widely used in fisheries, ecological impact assessments, and ecological restoration studies. It has been successfully applied to the evaluation and prediction of habitat changes of O. bartramii (Igarashi et al, 2018;Yu et al, 2020). A reliable proxy of species abundance and distribution is crucial to the model.…”
Section: Discussionmentioning
confidence: 99%
“…The HSI model has been widely used in fisheries, ecological impact assessments, and ecological restoration studies. It has been successfully applied to the evaluation and prediction of habitat changes of O. bartramii (Igarashi et al, 2018;Yu et al, 2020). A reliable proxy of species abundance and distribution is crucial to the model.…”
Section: Discussionmentioning
confidence: 99%
“…fresher waters (Tian et al, 2009). The neon flying squid are often found at the edges of warm-core rings for better feeding conditions (Igarashi et al, 2018). When the Oyashio Current reaches to the northern edge of these young warm-core eddies, just north of the KE, it is reported that the abundance of the neon flying squid increases there (Igarashi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While there are quite a vast number of studies looking at the patterns of suitable habitats for neon flying squid using the species distribution modeling approach [22,[43][44][45], the framework of analyses implemented in the present study provided both qualitative and quantitative means of elucidating the effects of the dominant modes of climatic variability in the North Pacific Ocean at a decadal time-scale. Our results underpinned the differences in the temporal trends for suitable squid habitat across climatic transitions and, more importantly, afforded a quantitative estimate of the spatial changes in the squid habitat suitability over time.…”
Section: Discussionmentioning
confidence: 99%